2011
DOI: 10.1002/ptr.3440
|View full text |Cite
|
Sign up to set email alerts
|

Emblica officinalis Corrects Functional, Biochemical and Molecular Deficits in Experimental Diabetic Neuropathy by Targeting the Oxido‐nitrosative Stress Mediated Inflammatory Cascade

Abstract: Diabetic neuropathy is one of the most common microvascular complications of diabetes mellitus which affects more than 50% of diabetic patients. Diabetic neuropathic pain is amongst the most difficult types of pain to treat mainly due to the lack of understanding of its etiology and inadequate relief with available drug therapy. The present study targeted oxidative stress mediated nerve damage in diabetic rats using an aqueous extract of Emblica officinalis, a potent natural antioxidant. Diabetic rats exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 56 publications
0
33
0
1
Order By: Relevance
“…The study conducted by Tiwari et al, demonstrated that E. officinalis extracts not only attenuated the diabetic condition but also reversed neuropathic pain through modulation of oxidative-nitrosative stress in diabetic rats. [33] Even Kumar et al, investigated flavonoid rich fruit extract of E. officinalis in type II diabetes induced diabetic neuropathy in male Sprague-Dawley rats. Treatment with E. officinalis extract (EOE) in diabetic rats displayed a significant increase in tail flick latency in hot immersion test and pain threshold level in hot plate test compared to control rats.…”
Section: Metabolic Syndromementioning
confidence: 98%
“…The study conducted by Tiwari et al, demonstrated that E. officinalis extracts not only attenuated the diabetic condition but also reversed neuropathic pain through modulation of oxidative-nitrosative stress in diabetic rats. [33] Even Kumar et al, investigated flavonoid rich fruit extract of E. officinalis in type II diabetes induced diabetic neuropathy in male Sprague-Dawley rats. Treatment with E. officinalis extract (EOE) in diabetic rats displayed a significant increase in tail flick latency in hot immersion test and pain threshold level in hot plate test compared to control rats.…”
Section: Metabolic Syndromementioning
confidence: 98%
“…The latency to the first sign of paw licking or jump response to avoid the heat was taken as an index of the pain threshold; the cut off time was 10 s in order to avoid damage to the paw [39].…”
Section: Experimental Designmentioning
confidence: 99%
“…In this test, mice were individually placed on a hot plate (Eddy's hot plate) with the temperature adjusted to 55 ± 1 C. The latency to the first sign of paw licking or jump response to avoid the heat was taken as an index of the pain threshold; the cut-off time was 10 s in order to avoid damage to the paw (Tiwari et al, 2011).…”
Section: Hot Plate Test (Thermal Hyperalgesia)mentioning
confidence: 99%